Behavioral Health and Personal Hygiene Practices in Coastal Areas: A Literature-Based Analysis - Najmasari, Neyza Farah; Ais, Hasna Rahadatul; Adiwinoto, Ronald Pratama (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Coastal communities face distinctive health challenges influenced by their geographical location and lifestyle. This scoping review aims to elucidate health problems, health behavior, and strategies to ameliorate health disparities among coastal residents within the last 5-10 years. A comprehensive search was conducted following the Arksey and O’Malley framework using databases such as PubMed, Google Scholar, and GARUDA (Indonesian Journal Database). Studies were included if they focused on human populations in coastal zones, addressed hygiene or behavioral health, and were published in English or Indonesian; purely clinical trials or non-peer-reviewed reports were excluded. A total of 10 articles were reviewed, encompassing diverse health aspects among coastal residents. The reviewed articles identified that sanitation-related issues (n=6) and skin infections (n=4) were the most prevalent health concerns. These encompassed high rates of open defecation, water-borne diseases, and infections prevalent in young children. Common factors contributing to these health challenges included harsh environmental salinity, limited access to clean drinking water, and cultural practices. Health behaviors of coastal residents were also highlighted, showcasing significant gaps in handwashing compliance and domestic waste management. Strategies to address these concerns involved multifaceted approaches, emphasizing education, sanitation improvements, and stakeholder engagement. Coastal residents face multifaceted health challenges influenced by their environment, socio-cultural practices, and limited access to resources. Addressing these issues necessitates holistic interventions that integrate community engagement, hygiene education, and infrastructure improvements, with active youth involvement to enhance sanitation. The findings underscore the urgency of tailored strategies to improve the health outcomes and well-being of coastal communities.